Management of OSAS: The ELIBA® Device Can Help the Patient? - Eleonora Ortu; Davide Pietropaoli; Alessandra Mummolo; IAPNOR; Mario Giannoni; Annalisa Monaco (Hindawi Limited, 2020)
Obstructive sleep apnea syndrome (OSAS) is one of the most challenging diseases to treat in medicine. Here, the authors describe a case of OSAS treated with a lingual elevator of Balercia (ELIBA®). The patient, a forty-five-year-old Caucasian male, had a chief complaint of numerous episodes of nocturnal apnea. After several visits with specialists, a polysomnographic examination was performed, in which the patient's apnea hypopnea index (AHI) was 30.4, and a lingual elevator was prescribed. The lingual elevator helped to keep the patient's tongue in the correct position and prevented the tongue from reverting back to the soft tissue spaces in the mouth. After six months of treatment with the lingual elevator and dietary adjustments, the patient's AHI decreased to 11.6. This simple yet customizable approach is a comfortable and easy option for patients to reduce night apnea episodes.